PENGEMBANGAN MODUL SOSIOLOGI BERBASIS MULTIKULTURAL - Nunuk Dian Anggraeni; Sudjarwo Sudjarwo; M. Thoha B.S. Jaya (Faculty of Teacher Training and Education, University of Lampung, 2015)
The purpose of this developmental research was to produce a sociology module based on multicultural students which was attractive and feasible, and foster multicultural education which is used in learning, and to determine the effectiveness of teaching materials to improve the learning outcomes. The research method used was Research and Development. The result of this development research: the needs of multicultural based sociology textbooks, which use student performance assessment with the assessment results in five groups and all groups, the average results of learning in class experiments using the textbook which is the result of learning development was higher than the average results of study in control class which is not using the product development results. Completeness of experimental class classical learning results reach the minimum, while the control class classical learning completeness reach less the minimum.Penelitian pengembangan ini bertujuan menghasilkan modul sosiologi berbasis multikultur pada siswa yg menarik dan layak, serta menumbuhkan pendidikan multikultural digunakan dalam pembelajaran, dan untuk mengetahui efektifitas bahan ajar dalam meningkatkan hasil belajar. Metode penelitian yang digunakan adalah Research and Development. Hasil penelitian pengembangan dapat disimpulkan: berdasarkan kebutuhan buku ajar sosiologi, menggunakan penilaian kinerja siswa dengan hasil penilaian dalam lima kelompok dan semua kelompok, rata-rata hasil belajar pada kelas eksperimen yang belajar dengan menggunakan buku ajar hasil pengembangan lebih tinggi dari rata-rata hasil belajar kelas kontrol yang belajar dengan tidak menggunakan produk hasil pengembangan. Ketuntasan hasil belajar klasikal kelas eksperimen mencapai batas minimal, sedangkan kelas kontrol ketuntasan belajar klasikal kurang mencapai batas minimal.Kata kunci: modul, multikultural, pengembangan